Reduced Plasma Dopamine-β-Hydroxylase Activity Is Associated With the Severity of Bipolar Disorder: A Pilot Study - Sun, Zuoli; Bo, Qijing; Mao, Zhen; Li, Feng; He, Fan; Pao, Christine; Li, Wenbiao; He, Yi; Ma, Xin; Wang, Chuanyue (Frontiers in Psychiatry, 2021)
Dopamine-β-hydroxylase (DβH) is an enzyme converting dopamine to norepinephrine, a key neurotransmitter in mood disorders, such as major depressive disorder (MDD) and bipolar disorder (BD). Due to overlapping symptomology of unipolar and bipolar depression, the present study attempted to explorer if the plasma DβH activity could discriminate the depressive episodes of BD from MDD. The aim of this study was to compare the plasma DβH activity among MDD patients (n = 104), BD patients (n = 101), and healthy controls (n = 160). Clinical characteristics and cognitive function were assessed using the Young Mania Rating Scale (YMRS), Hamilton Depression Scale (HAM-D), Hamilton Anxiety Scale (HAM-A), Patient Health Questionnaire-9 (PHQ-9), and Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Our data showed a lower plasma DβH activity in patients with BD, not MDD, than that in controls. For the BD patients, the plasma DβH activities were negatively correlated with HAM-D scores and HAM-A scores. However, there was no significant correlation between plasma DβH activity and severity of depressive symptoms in MDD patients. No significant correlation between DβH activities and cognitive assessments neither in BD nor in MDD patients. The present study provides evidence that BD is associated with decreased circulating DβH activity.